Efeito residual de intervenções mecânicas para descompactação do solo manejado sob sistema plantio direto - Drescher, Marta Sandra (2011)
The compaction became one of the main causes for soil degradation in agricultural areas, being directly related to the soil management system adopted. This situation can be observed in the Brazil humid subtropical climate area, by verification of the structural degradation of the soil subsuperficial layer, perceptible, in areas managed under no-till system (NTS), by alterations of soil physical properties, morphologic alterations of roots and perception, occasional, of crop yield reduction. In this sense, this work aimed at to generate knowledge about the residual effect of mechanical interventions for descompaction of soil managed under n0-till, conjugated to the mechanism of soil breaking used in drillers, about physical parameters of the soil, crop yield and force exercised on the agricultural tractor bar. For this, was carried out a study in the municipal district of Coxilha, in the northern area of Rio Grande do Sul, under a long duration experiment of Embrapa - Wheat. This experiment was installed in the year of 2001, in a farming area with eight year-old report under NTS. In that area, annual mechanical interventions were accomplished, by soil plowing and chiseling, previous the implantation of the summer crop. The adopted experimental design was random blocks with subdivided plots, with three repetitions. The treatments were a witness, which was the uninterrupted maintenance of NTS by 16 years and treatments constituted by six periods of time of NTS (7,5; 6,5; 5,5; 4,5; 3,5 and 2,5 years) after chiseling and, the same periods of NTS after plowing. The driller equipped with disks and with knife+disks, for the fertilizer placement in the sowing furrow, constituted the split-plots The results indicated that the mechanical intervention in soil managed under consolidated no-tillage through the soil chiseling or plowing, has potential to mitigate the ephemeral compaction and promote the improvement of soil structure, with a residual effect up to two years and half after the intervention. This residual effectt did not change the parameters of soybean grain yield in the crop year 2008/2009 and the force exercised on the agricultural tractor drawbar, compared to the area managed for 16 years under consolidated no-till. Moreover, the soil breaker mechanism, type knife + disk, which equips the no-till driller, was more effective in changing the evaluated parameters than the residual effect of mechanical intervention of chiseling or plowing the soil managed under comsolidated no-till. In this sense, the use of elements of soil breakers, like knife of deep action, designed to work in the compacted layer by no-till drillers, promoted mitigation of soil compaction in the 7-15 cm layer, by increasing soil macroporosity and reduction of microporosity, bulk density, soil penetration resistance and mechanical force exerted on the farm machinery drawbar, compared with the use of drillers equipped only with discs.